Outcomes of stage IIB osteosarcoma treated by limb salvage surgery using extracorporeally irradiated (ECI) autograft (Medical Journal of Indonesia, 2011)
Background: Extracorporeally irradiated (ECI) technique is an alternative of limb salvage procedure in treatingÂ osteosarcoma regarding limitation of endoprosthesis and allograft. This study evaluated the outcomes of limb salvageÂ surgery using extracorporeally irradiated (ECI) autograft and its correlation with patientâs characteristics.Methods: Retrospective cohort design was performed to study 20 patients with stage IIB osteosarcoma treated byÂ ECI autograft from 1995 to 2008. Survival, local recurrence, metastases, complications, union time and functionalÂ score based on Musculoskeletal Tumor Society scoring system-(MSTS) were evaluated. Kaplan-Meier methodÂ was used to describe survival, local recurrence free survival, and metastases free survival. The correlation amongÂ patientâs characteristics that were age, gender, duration, site of tumor size, type of osteosarcoma, SAP (serum alkalineÂ phosphatase) level, type of biopsy, and type of Huvos were analyzed by Log rank test. Chi-square test was used to analyzeÂ the correlation between MSTS score and patientâs characteristics, local recurrence, metastases, complications.Results: Five-year survival was 54.97 Â± 9.8 %, five-year local recurrence free survival was 66.5 Â± 7.6%, and fiveÂ year metastasis-free survival was 57.13 Â± 10.04%. Six patients died, five were due to lung metastases and one due toÂ complication of chemotherapy. Three underwent amputation after local recurrence. Kaplan-Meier curve showed thatÂ a good type of Huvos (III, IV) always gave better survival, local recurrence free survival, and metastases free survivalÂ than poor type of Huvos (I,II). Normal SAP level gave better local recurrence free survival compare to increased levelÂ of SAP. Mean of union rate was 8.13 months. MSTS mean score was good (70.63%) in patients with no evidenceÂ of disease. MSTS score was poor in patients with local recurrence (p = 0.025), metastases (p = 0.01), complicationsÂ (p = 0.03), and the combined of those three outcomes (p = 0.001).Conclusions: Functional outcome was poor in patients with local recurrence, metastases, and complications. SAP levelÂ and type of Huvos could be studied further as predictive factors for the outcomes (survival, local recurrence, metastases).Â (Med J Indones 2011; 20:131-7)Keywords: extracorporeally irradiated autograft (ECI), osteosarcoma stage IIB, outcomes